Dialectics of Islam and Bengal: A Study of the Da'wah Strategy of the Mafia Sholawat in Java - Junanah, Junanah; Safitri, Edi; Asroni, Ahmad; Susilo, Mohamad Joko (Universitas Ahmad Dahlan, 2025)
The research aims to determine: the philosophical, doctrinal, and sociological foundations behind the da'wah orientation; da'wah strategy; and the transformation of religious prayer Mafia congregations. This qualitative research uses the method of observation, documentation, and interviews. The results showed that: Gus Ali Gondrong with his Mafia Sholawat preferred the Bengali community as the object of his da'wah. Gus Ali Gondrong's da'wah strategy used various media including: physical media, verbal, and amaliah media. Sholawat accompanied by music and Sufi dances, the tausyiah conveyed by Gus Ali was non-judgmental and able to embrace the bengal community. Third, Gus Ali Gondrong's da'wah strategy uses Berger and Luckmann's theoretical framework by using a dialectical process experienced by humans through three momentums, namely: externalization, objectivation, and internalization. The transformation of the congregation is evidenced by changes in attitudes, behavior, and commitment to religious teachings; feel like a better human being, act the right way; as well as a change in the principle of religious life towards a more firm and clear direction. This research can contribute to development of more contextual and effective da'wah theories and strategies in dealing with ignorance, especially in the Javanese context.